Studies On Dielectric Properties of Calcium Copper Titanate at Different Sintering Conditions - Kumar, Ravindra (My University, 2010)
CaCu3Ti4O12 (CCTO) electroceramic was prepared by a solid state reaction technique from CaCO3, CuO and TiO2 powders. Processing involved the raw material and their and milling, calcination, pellet forming and sintering processes. The calcination of CCTO was carried out at 1000°C for 24 hours in glowber furnace. The formation of CCTO is confirmed by XRD. Samples were sintered at different temperature in order to improve phase structure,density, homogeneity, morphology and dielectric properties of CCTO ceramics. The morphology and size of the grains of the pellets were observed using scanning electron microscopy (SEM). SEM images show that the grain size of sintered samples is increasing with increase of sintering temperature. The dielectric properties of the samples were analyzed in the wide range of frequency (102 - 107 Hz ).Dielectric studies shows that dielectric constant is increasing with increasing sintering temperature and holding time while tanδ remains almost same after 2 h heat treated sample and decreased for 10 h. It is found that on increasing grain size which is obtained by rising the sintering temperature, the dielectric properties are enhanced.
M.Tech.
Keywords: Dielectric , calcium copper titanate